Open university for older adults: training seniors as research consultants. - Oliveira, Mariele Gobo de; Almeida, Graziela Maria Ferraz de; Vieira, Matheus Cardoso Moraes; Lima, Fernanda Maria Alves; Lemos, Cassiane de Santana; Rodrigues, Caroline Iaiz; Patini, Mayara Salles Gasparini; Scetta, Gabriela Pereira; Avila, Marla Andréia Garcia de (Anna Nery School Journal of Nursing / Escola Anna Nery Revista de Enfermagem, 2025)
Objective: to describe the experience of researchers in the design and implementation of an event entitled "Training Patients as Research Consultants". Method: experience report based on an event held in October 2024 by the Open University for Older Adults, as part of the activities of the National Festival Public and Patient Involvement (PPI) – Ireland 2024, at a public university in the interior of São Paulo. The event program was structured in five stages: welcome and introductions; "fact or fake" game; contextualization of research methodology; specialty groups; and identification of research partners. Results: twenty-five older adults participated in the event. The program enabled active engagement and provided insights into participants’ level of understanding of scientific information. The specialty groups cardiology, gastroenterology intestinal surgery, neurosurgery, and nephrology — served as listening spaces for participants’ experiences and for sharing what they consider to be research priorities. Conclusion and implications for practices: the experience highlighted the importance of including patients and caregivers in the process of formulating research questions. Although this approach is still emerging in Brazil, it offers great potential for fostering research that is more responsive to societal needs, reinforcing the link between science and the community.